Removal of Uranium (VI) with Iron Nanoparticles - Crespi, Julieta (2016)
In this work, the removal efficiency of U(VI) from water using commercial nanoparticles of zerovalent iron (nZVI) (NANOFER 25, NANO IRON s.r.o.) and magnetite (nM) (NanoFe®, Nanotek SA) was evaluated. Batch experiments were carried out in a jacketed reactor with a vertical paddle stirrer, using UO2(NO3)2 solutions([U(VI)]0 = 0.25 mM = 59.5 mg L-1) at pH 5.3. The nanoparticles (initially suspended in water) were added tothe U(VI) solution to achieve different Fe:U(VI) molar ratios (MR) in the range of 1 to 100. U(VI) removal with nZVI and nM at MR 4 and dissolved oxygen (DO) levels higher than 0.1 mg L-1 were rather efficient, reaching in both cases a final removal of 65 %. Under these conditions, uranium removal strongly depends on thepresence of DO, decreasing with increasing DO. When 40 and 100 MR were used, a complete U(VI) removal in the first 15 min of treatment was observed, and oxygen was consumed reaching negligible DO levels (below0.1 mg L-1). With MR = 4 and DO levels below 0.1 mg L-1 (achieved by N2 bubbling), removal of U(VI) wascomplete in 60 min of reaction for both types of nanoparticles. Although the trend of the removal curves was similar, the advantage of nM is that very low levels of iron in solution (as Fe(total)), below 1 mg L-1, were observed during the whole reaction time, while it was 5 mg L-1 for nZVI at the end of the run, mainly as Fe(II). Analysis of the final solids by XANES and Raman spectroscopies revealed the presence of uranium, probably as UO2.